2022
DOI: 10.3389/fneur.2022.875178
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic cueing, dance, resistance training, and Parkinson's disease: A systematic review and meta-analysis

Abstract: ObjectivesThe aim of the present systematic review and meta-analysis was to synthesize evidence associated with the functional and clinical effectiveness of rhythmic cueing, dance, or resistance training (RT) on motor and non-motor parameters in Parkinson's Disease patients, and to provide a comparative perspective not offered by existing systematic reviews.MethodologyEligibility criteria for selecting studies retained no restrictions in methodological design and included interventions of rhythmic cueing, danc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 99 publications
0
9
0
Order By: Relevance
“…Previous studies have shown that strength training and aerobic training play important roles in improving motor function (Carvalho et al, 2015; Zhou et al, 2022). Because strength training builds muscle strength and improves muscle weakness caused by PD (Karpodini et al, 2022) and aerobic exercise improves blood flow and promotes neuroplasticity (Petzinger et al, 2013; Zhou et al, 2022), these effects may play a beneficial role in improving motor function in people with PD. Our study supports the benefits of both physiotherapy treatments in terms of motor symptom severity, but this effect does not achieve clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that strength training and aerobic training play important roles in improving motor function (Carvalho et al, 2015; Zhou et al, 2022). Because strength training builds muscle strength and improves muscle weakness caused by PD (Karpodini et al, 2022) and aerobic exercise improves blood flow and promotes neuroplasticity (Petzinger et al, 2013; Zhou et al, 2022), these effects may play a beneficial role in improving motor function in people with PD. Our study supports the benefits of both physiotherapy treatments in terms of motor symptom severity, but this effect does not achieve clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
“…When considering the effect of the different intervention types on walking speed, all four intervention types had a positive effect but did not show statistical significance. Previous studies have also reported on the limited effectiveness of strength training, dance, and aerobic exercise in improving walking speed (Karpodini et al, 2022; Radder et al, 2020). However, some reviews have found that Tai Chi and BGT can significantly improve walking speed (Radder et al, 2020; Wu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research in PD has revealed that rhythmic training seems to improve synchronization of neural activity in the brain, especially in the basal ganglia [ 12 ]. A systematic review evaluating the effect of rhythmic auditory stimulation on motor and non-motor parameters in PD patients revealed positive effects on gait parameters and mobility [ 13 ]. Another study revealed that rhythmic movement interventions that incorporate visual and auditory cues can improve sensorimotor integration [ 14 ].…”
Section: Introductionmentioning
confidence: 99%